«Science for Truth and the Good». The Spanish Council for Scientific Research and the aim to control de historiographic production under de Francoist regime - Fernández Gallego, Alba (Hispania Nova, 2021)
This paper addresses the configuration of the CSIC within the framework of the end of the Civil War, which cab understood as occupation warfare. The main hypothesis is that its creation responded to the need of a State to create its own institutionality as it was born during a conflict. This meant the opportunity to occupy the academic and research institutions for the academic staff that had been relegated during the previous decades. Firstly, my article will analyze the breakdowns and continuities at CSIC in relation to the academic background and, concretely, to the Junta para Ampliación de Estudios. Secondly, the official discourses launched by the institution will be examined. Finally, historiographic production will be addressed more concretely by examining some CSIC journals.